2021
DOI: 10.1177/08948453211050654
|View full text |Cite
|
Sign up to set email alerts
|

Living a Calling During COVID-19: A Resource Gain Perspective

Abstract: Massive disruptions to work and threats to employee well-being due to the coronavirus disease 2019 (COVID-19) pandemic have highlighted the need to identify resources which enable employees to gain other valuable resources. Using a resource gain perspective, we examined the role of living a calling as a potentially robust resource, enabling employees to gain work readiness during the COVID-19 pandemic, and, in turn, resulting in a greater well-being in the form of lower job strain. Using a sample of clergy ( N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…It is shown that the employees with a strong career calling will show dedication and solidarity as well as motivation, exhibit increased courage and perseverance to overcome difficulties and have a stronger adaptability (Creed et al, 2020). They are capable of persisting in challenging work environments, often at the expense of their energy, time and interests (Terry and Cigularov, 2021). Consequently, these employees proactively pursue their goals, embrace greater risks and attain their ultimate objectives through ongoing trial-and-error learning, accumulating experience and reflective analysis of past behaviors.…”
Section: Organizational Crisis Career Calling and Taking Chargementioning
confidence: 99%
“…It is shown that the employees with a strong career calling will show dedication and solidarity as well as motivation, exhibit increased courage and perseverance to overcome difficulties and have a stronger adaptability (Creed et al, 2020). They are capable of persisting in challenging work environments, often at the expense of their energy, time and interests (Terry and Cigularov, 2021). Consequently, these employees proactively pursue their goals, embrace greater risks and attain their ultimate objectives through ongoing trial-and-error learning, accumulating experience and reflective analysis of past behaviors.…”
Section: Organizational Crisis Career Calling and Taking Chargementioning
confidence: 99%
“…The sense of being called, the meaning attached to work, and a strong passion for their job motivate people to exert their effort for the benefits of others and overlook possible external obstacles in pursuing their callings (Dobrow & Heller, 2015). Within the framework of the Conservation of Resources theory (COR; Hobfoll, 1989) and adopting a resource gain perspective, perceiving a calling can be seen as a resource itself that enables other resources (Terry & Cigularov, 2021). Empirical evidence suggests that calling is related to many positive outcomes, e.g., to higher satisfaction, commitment, and performance (Duffy et al, 2018;Vianello et al, 2022).…”
Section: Work As a Calling In Healthcare Workersmentioning
confidence: 99%
“…At this aim, this study focuses on the construct of career calling, a positive orientation toward work that is linked with higher satisfaction, performance, engagement, and commitment. Career calling is considered a useful personal resource that fosters resilience and improves positive reactions (Creed et al, 2014;Terry & Cigularov, 2021). Research is emerging that focuses on changes and effects of calling during the pandemic (Andel et al, 2021;Uzunbacak et al, 2022;Zhou et al, 2020;Wei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some businesses were able to furlough employees, supported by the Government, while others had to lay off people or fully shutdown. While the COVID-19 pandemic is not completely over, the prognosis for the global economy is pessimistic, expecting a recession that will have implications for many individuals' careers, both in terms of financial security and health [1][2][3].…”
Section: Introductionmentioning
confidence: 99%